INFLUENCE BRAND AMBASSADOR, BRAND IMAGE, AND MOTIVATION IN THE INTEREST IN BUYING OF TOKOPEDIA ONLINE RETAIL CONSUMERS - Alfiyani; Kartika Dwi Chandra Sari; Slamet (Publikasi Inspirasi Indonesia, 2024)
E-commerce is a commercial transaction utilizing digital technology, ecommerce that has sprung up results in competition in attracting consumer buying interest. This study aims to determine the effect of brand ambassadors, brand image, and motivation on consumer buying interest in Tokopedia. This research method is quantitative with explanatory research type. The sample in this study were 155 respondents in Central Java who were Tokopedia consumers, using the conveniance sampling technique. Data were obtained through an online questionnaire and data processing using SEM-PLS analysis with the help of the SmartPLS 4 program application. The results of this study show that brand ambassadors, brand image, and motivation have a positive and significant effect on buying interest and brand ambassadors have a positive and significant effect on brand image. Suggestions for further research conduct research using variables that can influence buying interest, namely promotion, price, and shopping experience and increase the number of samples.